2022
DOI: 10.3389/fpsyt.2022.1015914
|View full text |Cite
|
Sign up to set email alerts
|

The impact of machine learning in predicting risk of violence: A systematic review

Abstract: BackgroundInpatient violence in clinical and forensic settings is still an ongoing challenge to organizations and practitioners. Existing risk assessment instruments show only moderate benefits in clinical practice, are time consuming, and seem to scarcely generalize across different populations. In the last years, machine learning (ML) models have been applied in the study of risk factors for aggressive episodes. The objective of this systematic review is to investigate the potential of ML for identifying ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Previous research has shown an acceptable power for ML models in predicting VB in populations broader than SSD patients ( 68 , 69 ). In this article, we reviewed the role of ML in predicting VB in patients with SSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown an acceptable power for ML models in predicting VB in populations broader than SSD patients ( 68 , 69 ). In this article, we reviewed the role of ML in predicting VB in patients with SSD.…”
Section: Discussionmentioning
confidence: 99%
“…patients (68,69). In this article, we reviewed the role of ML in predicting VB in patients with SSD.…”
Section: Key Findingsmentioning
confidence: 99%
“…Cell phones are readily trackable, as are healthcare clinicians via proximity badge readers. Integrating these data with patient and visitor data are ideal for an ML/AI approach to assess HV risk or track its occurrence (68). Systems such as the Evolv weapons detection system can provide actionable data, especially when coupled with AI-driven facial recognition software outside as well as inside the healthcare facility (69).…”
Section: Role Of Machine Learning/augmented Intelligence In Violence ...mentioning
confidence: 99%
“…Moreover, computational methods have helped to understand the impact of different sources of information in neurodegenerative disorders ( 36 ) or elucidating individual and contextual factors determining complex behaviors such as violence ( 37 ).…”
Section: Computational Models Applied In Neuroscience and Psychiatrymentioning
confidence: 99%